2016
DOI: 10.1103/physreve.93.012202
|View full text |Cite
|
Sign up to set email alerts
|

Uniform framework for the recurrence-network analysis of chaotic time series

Abstract: We propose a general method for the construction and analysis of unweighted ε-recurrence networks from chaotic time series. The selection of the critical threshold ε_{c} in our scheme is done empirically and we show that its value is closely linked to the embedding dimension M. In fact, we are able to identify a small critical range Δε numerically that is approximately the same for the random and several standard chaotic time series for a fixed M. This provides us a uniform framework for the nonsubjective comp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 47 publications
3
38
0
Order By: Relevance
“…A critical range of threshold ∆ǫ is selected for the construction of the network whose minimum is chosen with the standard condition that there exists a single giant component in the resulting RN. We have shown that [37] this critical range is approximately identical for several chaotic systems and white noise and de-pends only on the embedding dimension M. The threshold values used here for the construction of the network are ǫ = 0.06, 0.10, 0.14 and 0.18 for M varying from 2 to 5 respectively. The scheme has been effectively employed to study the influence of noise on the structure of chaotic attractors [38] and for the analysis of light curves from a prominent black hole system [39].…”
Section: Recurrence Network and Entropy Measurementioning
confidence: 84%
See 1 more Smart Citation
“…A critical range of threshold ∆ǫ is selected for the construction of the network whose minimum is chosen with the standard condition that there exists a single giant component in the resulting RN. We have shown that [37] this critical range is approximately identical for several chaotic systems and white noise and de-pends only on the embedding dimension M. The threshold values used here for the construction of the network are ǫ = 0.06, 0.10, 0.14 and 0.18 for M varying from 2 to 5 respectively. The scheme has been effectively employed to study the influence of noise on the structure of chaotic attractors [38] and for the analysis of light curves from a prominent black hole system [39].…”
Section: Recurrence Network and Entropy Measurementioning
confidence: 84%
“…The choice of the parameter ǫ is crucial for the construction of the RN to ensure that the resulting network is a proper representation of the embedded attractor. We have recently proposed a scheme [37] for the construction of RN where the value of ǫ is automated for a given embedding dimension M.…”
Section: Recurrence Network and Entropy Measurementioning
confidence: 99%
“…7 taking time series from the Lorenz attractor (upper panel) and white noise (lower panel) and computing the degree distribution for various M values. It is also known [35] that the variation of the degree distribution with M for white noise is similar to that of the surrogate data. However, the above observations regarding convergence are subjective since the distributions for two M values can never coincide exactly.…”
Section: Analysis Of Synthetic Datamentioning
confidence: 89%
“…This is achieved by the proper choice of the recurrence threshold ǫ and the embedding dimension M. We have recently shown [35] that the value of ǫ is closely related to the choice of M. We have also proposed a general method for the construction of RN from a time series, which we follow here. The basic criterion that we use to select the recurrence threshold ǫ is that the resulting RN should have a giant component and the ǫ value obtained using this criterion is approximately the same for different time series for a given M, due to the uniform deviate transformation.…”
Section: Recurrence Network and Related Measuresmentioning
confidence: 99%
See 1 more Smart Citation